Somatic Mutations in Fruit Trees: Causes, Detection Methods, and Molecular Mechanisms - Seunghyun Ban; Je Hyeong Jung (Plants, 2023)
Somatic mutations are genetic changes that occur in non-reproductive cells. In fruit trees, such as apple, grape, orange, and peach, somatic mutations are typically observed as “bud sports” that remain stable during vegetative propagation. Bud sports exhibit various horticulturally important traits that differ from those of their parent plants. Somatic mutations are caused by internal factors, such as DNA replication error, DNA repair error, transposable elements, and deletion, and external factors, such as strong ultraviolet radiation, high temperature, and water availability. There are several methods for detecting somatic mutations, including cytogenetic analysis, and molecular techniques, such as PCR-based methods, DNA sequencing, and epigenomic profiling. Each method has its advantages and limitations, and the choice of method depends on the research question and the available resources. The purpose of this review is to provide a comprehensive understanding of the factors that cause somatic mutations, techniques used to identify them, and underlying molecular mechanisms. Furthermore, we present several case studies that demonstrate how somatic mutation research can be leveraged to discover novel genetic variations. Overall, considering the diverse academic and practical value of somatic mutations in fruit crops, especially those that require lengthy breeding efforts, related research is expected to become more active.